Development of temporal rainfall pattern for Sarawak - Julian Leslie, Anyie (Universiti Malaysia Sarawak, UNIMAS, 2009)
In the study of the design rainfall, the information on rainfall duration, average rainfall intensity and temporal rainfall pattern is important. This project is to develop of temporal rainfall pattern for Sarawak since temporal pattern for Sarawak is still not available Hydrological Procedure No. 1 (HP-No.1). Urban Stormwater Management Manual for Malaysia (MASMA) had developed the temporal pattern for design storms in Peninsular Malaysia and the temporal rainfall pattern for East Coast of Peninsular Malaysia were adopted for Sarawak. Temporal rainfall pattern is important in flood estimation which is useful in engineering practice such as design of hydrologic structures, flood plain management, river ecology studies and flood insurance studies. As mentioned in MASMA, the recommended technique by the Australian Rainfall and Runoff (AR&R) known as the ‘Method of Average Variability’ and method in Hydrological Procedure No.1-1982 are used to develop temporal rainfall patterns. 5 minutes rainfall data from year 1998 to year 2006 for 10 selected rainfall stations in Sarawak is obtained from Department of Irrigation and Drainage (DID) Sarawak to conduct this project. The temporal rainfall patterns developed are for 10 minutes,15 minutes, 30 minutes, 60 minutes, 120 minutes, 180 minutes and 360 minutes duration. After obtaining the temporal rainfall patterns, the patterns are to be compared to the patterns for East Coast of Peninsular Malaysia. It is expected that the design temporal rainfall pattern obtained can contribute to Sarawak hydrological research.